Improving Elementary School Students’ Numeracy Skills Through the GASING Method in Maybrat - Atty Marta Kambu; Yunus Abidin; Dede Trie Kurniawan; Atty Marta Kambu; Yunus Abidin (Universitas Negeri Malang, 2026)
Numeracy skills are essential competencies for 21st-century learning, enabling students to understand quantitative information, apply mathematical reasoning, and solve everyday problems. However, elementary school students in Indonesia, particularly in disadvantaged, frontier, and outermost regions such as Maybrat Regency, continue to face challenges in developing numeracy skills. This study aimed to examine the effectiveness of the GASING Method (Gampang, Asyik, dan Menyenangkan; Easy, Fun, and Enjoyable) in improving elementary students’ numeracy skills in Maybrat Regency. A quantitative approach with a quasi-experimental One-Group Pretest–Posttest Design was employed. The sample consisted of 37 students from four elementary schools selected through total sampling. Data were collected through numeracy tests administered before and after the intervention and analyzed using descriptive statistics, Normalized Gain (N-Gain), and the Wilcoxon Signed Rank Test. The findings showed a significant improvement in students’ numeracy skills after the implementation of the GASING Method. The mean score increased from 29.73 on the pretest to 76.76 on the posttest, with an N-Gain score of 0.63, indicating a moderate level of improvement. The Wilcoxon test also revealed a statistically significant difference between pretest and posttest scores (p < 0.05). These results indicate that the GASING Method is effective in enhancing numeracy skills through systematic and concept-oriented learning. The findings provide empirical evidence for developing contextual and meaningful numeracy instruction, particularly in elementary education within disadvantaged, frontier, and outermost regions.